Performance of a PLC system in impulsive noise with selection combining - Dubey, Ankit; Mallik, Ranjan K.; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2012)
This paper proposes a selection combining (SC) scheme for a power line communication (PLC) system with binary phase-shift keying. The main purpose is to utilize multiple of independent and non-interfering channels to send an information-bearing signal and to use SC at the receiver end to improve the reliability of the PLC system. The fading coefficient of each PLC channel is modeled by a log-normal distribution, and to include the effects of both background noise and impulsive noise, the additive noise samples are taken from a Bernoulli-Gaussian process. We obtain a closed-form approximation of the bit error rate and an expression for the outage probability of the proposed scheme. The merit of the L-channel PLC system with SC when compared with a single channel PLC system over different fading and impulsive noise scenarios is demonstrated through numerical results. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Bernoulli-Gaussian process; binary phase-shift keying (BPSK); bit error rate (BER); Lambert L-function; log-normal fading; power line communication (PLC); selection combining (SC)